Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Dalam Perspektif Islam (Studi Kasus Bank Muamalat Balai Kota Medan) - Nasution, Rahmi Andini; Mujiatun, Siti (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This research was conducted with the aim of analyzing the effect of leadership style and work motivation on employee performance in an Islamic perspective (a case study of bank muamalat city hall of Medan). The research method used in this study is quantitative research and data collection techniques in this study using a questionnaire. The data analysis used in this research is data quality test, classic assumption test, multiple linear regression test, hypothesis test and determination test. Based on the results of the study, it was shown that the variable t (partial) test results showed that the significant value of leadership style (X1) on employee performance at Bank Muamalat Balai Kota Medan (Y) was 0.001 <0.05 and the value of t count was 4.301 > t tableÂ  2,012 ,so Ho1 is rejected and Ha1 is accepted. As for seeing the magnitude of the influence of leadership style on employee performance at bank muamalat, look at the "Beta" table in the Standardized Coefficients column. From the table above, it is obtained that the Beta for the leadership style variable (X1) is 0.531 or 53.1%. This means that there is a significant influence of leadership style on employee performance. The results of the t (partial) test show that the significant value of work motivation (X2) on employee performance at bank muamalat (Y) is 0.000 <0.05 and the t count Â value is 4.108 > t table 2,012, then Ho2 is rejected and Ha2 is accepted. This means that partially there is significant influence from work motivation (X2) on employee performance at bank muamalat (Y). From the table above, it is obtained that the Beta value of the work motivation variable (X2) is 0.514 or 51.4%. This means that there is a significant influence of work motivation on employee performance.